Research and development project assessment and social impact - Ana Fernández; Jorge Cunha; Paula Ferreira; Madalena Araújo; Enrique Ares Goméz (Production)
Abstract Nowadays, organisations increasingly need to adapt to the fast evolution of markets and societies in our globalised world in order to be competitive. Therefore, it is essential to take the right decisions when it comes to invest in research and development (R&D) projects. However, an issue that has not been given much attention is how to measure the social impact (or return) of R&D projects. In this exploratory study, the findings of an analysis of how R&D projects are assessed and selected, including this social perspective, are presented. The methodology which has been used in this research includes both interviews and analysis of the data obtained through them. The major finding is that in the current situation the social impact is not taken into account, but is growing the awareness of this perspective among different types of organizations dealing with R&D activities.